Mandibular recontouring with polyetheretherketone (PEEK) patient-specific implants. Issue 4 (12th April 2022) - Nocini, Riccardo; D'Agostino, Antonio; Trevisiol, Lorenzo; Favero, Vittorio
Abstract : The definition of the mandibular angle profile is a common challenge for oral and maxillofacial surgeons. Accurate diagnosis and treatment planning are mandatory in order to properly manage soft and hard tissues. The use of several biomaterials is described in the literature. The present paper reports the treatment of a defect in the right mandibular angle in otomandibular syndrome sequelae by positioning polyetheretherketone (PEEK) patient-specific implants (PSI) in a 25-year-old patient who previously underwent orthognathic surgery. Satisfactory aesthetic results were achieved with no complications 12 months after surgery. Considering its advantageous physical properties and the low rate of postoperative complications reported in the literature, PEEK can increase the treatment options for recontouring not only the upper third and the middle third of the face, but also of the lower third, in particular in cases of large three-dimensional defects.